Antimicrobial activity of Streptomyces spp. isolates from vegetable plantation soil - Isnaeni Isnaeni; Idha Kusumawati; Mega Ferdina Suwito; Asri Darmawati; Ni Made Mertaniasih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
Fifteen Streptomyces isolates were isolated from soil in some different location on vegetable plantation at agriculture standard condition. The isolates were assessed for their antibacterial activity against Mycobacterium tuberculosis (MTB) ATCC H37RV and mycobacterial which isolated from Dr. Soetomo Hospital patients in Surabaya. The Interna-tional Streptomyces Project 4 (ISP4) and Middlebrook 7H9 (MB7H9) wwere used as growth or fermentation medium. The screening of inhibition activity was performed using turbidimetry and spot-test on agar medium. Results shown that 33.3% of the isolates (5 isolates) have anti-mycobacterial activities. The first line anti tuberculosis drug rifampicin, (RIF), ethambutol (EMB), isoniazid (INH), and pyrazinamide (PZA) were used as standards or positive controls with concentration 20 ppm. Optical density of crude fermentation broth concentrated from five isolates relatively lower than five anti-tuberculosis drug activity standard, although their activities against some microbial were similar to the stand-ard at spot-test. The most efficient isolate shown anti-mycobacterial activity was Streptomyces B10 which identified as Streptomyces violaceousniger. In addition, fatty acid methyl ester (FAME) profile of gas chromatography-mass spec-trometry chromatogram of each isolates were studied and compared to Streptomyces spp.